Seasonal Influenza Vaccine and Protection against Pandemic (H1N1) 2009-Associated Illness among US Military Personnel - Johns, Matthew C.; Eick, Angelia A.; Blazes, David L.; Lee, Seung-eun; Perdue, Christopher L.; Lipnick, Robert; Vest, Kelly G.; Russell, Kevin L.; DeFraites, Robert F.; Sanchez, Jose L. (PLOS ONE, 2010)
Introduction A novel A/H1N1 virus is the cause of the present influenza pandemic; vaccination is a key countermeasure, however, few data assessing prior seasonal vaccine effectiveness (VE) against the pandemic strain of H1N1 (pH1N1) virus are available. Materials and Methods Surveillance of influenza-related medical encounter data of active duty military service members stationed in the United States during the period of April–October 2009 with comparison of pH1N1-confirmed cases and location and date-matched controls. Crude odds ratios (OR) and VE estimates for immunized versus non-immunized were calculated as well as adjusted OR (AOR) controlling for sex, age group, and history of prior influenza vaccination. Separate stratified VE analyses by vaccine type (trivalent inactivated [TIV] or live attenuated [LAIV]), age groups and hospitalization status were also performed. For the period of April 20 to October 15, 2009, a total of 1,205 cases of pH1N1-confirmed cases were reported, 966 (80%) among males and over one-half (58%) under 25 years of age. Overall VE for service members was found to be 45% (95% CI, 33 to 55%). Immunization with prior season's TIV (VE = 44%, 95% CI, 32 to 54%) as well as LAIV (VE = 24%, 95% CI, 6 to 38%) were both found to be associated with protection. Of significance, VE against a severe disease outcome was higher (VE = 62%, 95% CI, 14 to 84%) than against milder outcomes (VE = 42%, 95% CI, 29 to 53%). Conclusion A moderate association with protection against clinically apparent, laboratory-confirmed Pandemic (H1N1) 2009-associated illness was found for immunization with either TIV or LAIV 2008–09 seasonal influenza vaccines. This association with protection was found to be especially apparent for severe disease as compared to milder outcome, as well as in the youngest and older populations. Prior vaccination with seasonal influenza vaccines in 2004–08 was also independently associated with protection.